2023
DOI: 10.55563/clinexprheumatol/4uc7e8
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus: one year in review 2023

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a wide range of clinical manifestations and a relapsing-remitting course. New data regarding pathogenic pathways, biomarkers and clinical manifestations of SLE are emerging, and new drugs and therapeutic protocols have been proposed to improve the control of disease activity. Furthermore, new insights into comorbidities and reproductive health in SLE patients are constantly emerging. This annual review aims to summarise the most relevant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In [2], the gene ITGA8 was discussed; see also [17]. However, this gene was not identified in our computation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [2], the gene ITGA8 was discussed; see also [17]. However, this gene was not identified in our computation.…”
Section: Discussionmentioning
confidence: 99%
“…The global SLE newly diagnosed population is estimated to be around 400,000 annually, and most of these people are women [1]. In the one year in review 2023 [2], the authors reviewed 93 published papers in 2022 and concluded new results and data have improved the understanding of SLE, although further studies and research are needed to improve the knowledge we have on this complex disease. Upon reviewing 120 published articles, the authors in [3] concluded that more robust immunological biomarkers are needed to better understand disease progression in individuals with SLE, including non-organ-specific SLE biomarkers and organ-specific SLE biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown why patients with SLE have a higher incidence of malignancies of the reproductive tract, but this may be attributable to the following: overlap with Sjogren’s syndrome, lupus-associated medications, viral infections, conventional cancer risk factors, and innate immune system abnormalities ( 11 ). SLE is characterized by the formation of numerous immune complexes through the binding of autoantibodies (anti-DNA and anti-histone antibodies) to their corresponding autoantigens ( 16 , 17 ), which are deposited throughout the body, activating the complement system and leading to tissue damage. Patients with SLE have an increased risk of developing malignancies due to the accumulation of DNA damage caused by autoantibodies that interfere with DNA repair ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…SLE is a chronic autoimmune condition with a complex and not yet fully clarified pathogenesis that results in heterogeneous clinical and serological disease manifestations. According to the setting of the One year in review series (1), we aim to provide a brief critical digest of the latest findings about SLE. We performed a MEDLINE search of English language articles published from 1 st January to 31st December 2023 using MESH terms and free text words for the following search keys: systemic lupus erythematosus AND biomarkers, clinical manifestations, patient-reported outcomes, comorbidities, phase III and post-marketing studies, registries, real-world evidence, preclinical and phase I-II clinical studies.…”
Section: Introductionmentioning
confidence: 99%